PENANAMAN NILAI-NILAI PELAJAR PANCASILA MELALUI PENCIPTAAN BUDAYA POSITIF DI SD LAZUARDI TURSINA BANYUWANGI - Nur Wiarsih; Kurniyatul Faizah; Zidniyati Zidniyati (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2023)
Pancasila is the philosophy of the Indonesian nation. Indonesian students should have character as the values contained in Pancasila. The values of Pancasila can be instilled through various strategies both directly in the learning process in the classroom, as well as the creation of a positive culture in schools. A positive culture in schools can be a productive medium for instilling Pancasila values for students. This study aims to describe the creation of a positive culture at SD Lazuardi Tursina Banyuwangi. This study used qualitative descriptive method. The subjects of the study were teachers and students at SD Lazuardi Tursina Banyuwangi. This study involved 7 teachers, consisting of 3 teachers from low grades and 4 teachers from high grades. The students involved in this study were 30 students divided into 10 students from low grades and 20 students from high grades. Data collection techniques are conducted through interviews, observation, and documentation. The results showed that the creation of a positive culture The positive culture developed by the school consists of religious habituation, structuring the learning environment, and project compassionated action. The school believes that the cultivation of Pancasila values is effective when carried out in habituation of daily life at school. Therefore, schools need to build a positive culture that guides children and teachers in interacting with all school residents.